Penggunaan Canva sebagai Bahan Ajar Materi Surat Lamaran Kerja untuk Meningkatkan Pembelajaran Bahasa Indonesia Kelas XII di SMKS 3 Idhata Curup - Yuni, Risti; Yuniati, Ira; Asmara, Adi (Indo-MathEdu Intellectuals Journal, 2024)
This article examines the use of Canva as a teaching tool for Indonesian language instruction on job application letters in the XII Fashion Design class at SMKS 3 Idhata Curup. The goal is to describe Canva's effectiveness in enhancing students' writing skills and comprehension. Canva, as an online design and visual communication tool, helps convey messages and information effectively. This research employs a quantitative method with a descriptive approach. The study shows that Canva is effective as a learning medium, improving writing skills, comprehension, and student engagement. Integrating digital technology like Canva enriches the learning experience and prepares students for the digital workforce. It is recommended that Canva or similar digital media be more widely used across various subjects to enhance the quality of education. Overall, the use of Canva in teaching job application letters in the XII Fashion Design class at SMKS 3 Idhata Curup yields positive results and is worth implementing